2015
DOI: 10.1038/hdy.2015.50
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and phenotypic influences on copulatory plug survival in mice

Abstract: Across a diversity of animals, male seminal fluid coagulates upon ejaculation to form a hardened structure known as a copulatory plug. Previous studies suggest that copulatory plugs evolved as a mechanism for males to impede remating by females, but detailed investigations into the time course over which plugs survive in the female's reproductive tract are lacking. Here, we cross males from eight inbred strains to females from two inbred strains of house mice (Mus musculus domesticus). Plug survival was signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 94 publications
2
28
0
Order By: Relevance
“…Here, we show that copulatory plugs that are ineffective at preventing female remating can still benefit their producers in a sperm competition context through subtle changes in rival male behaviour (Parker, ). Our results contribute to our understanding of the complex dynamics of copulatory plugs in house mice (Mangels et al ., ), and highlight the importance for investigating fitness consequences of male traits at different stages of reproductive competition.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we show that copulatory plugs that are ineffective at preventing female remating can still benefit their producers in a sperm competition context through subtle changes in rival male behaviour (Parker, ). Our results contribute to our understanding of the complex dynamics of copulatory plugs in house mice (Mangels et al ., ), and highlight the importance for investigating fitness consequences of male traits at different stages of reproductive competition.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to several studies that found high degrees of differences in expression of SFPs between manipulated sperm competition levels, the lack of group size, and thus sperm competition effect in M. lignano may therefore be explained by the existence of GEI. Overall, these results suggest that GEI could be widespread among seminal fluid production and this potentially can help explain the maintenance of standing genetic variation for seminal fluid proteins that were shown in some studies (for gene expression: Smith et al , 2009; Patlar et al , 2019; for protein abundance: Baer et al , 2012; Goenaga et al , 2015; Mangels et al , 2015). In fact, one can expect some genetic variation to be maintained for some SFPs because of the lack of fitness relation, thus selection do not act on but, considering their varying functions related tightly with successful reproduction, this can be unlikely a reason for standing genetic variation (Heifetz et al , 2001; LaFlamme et al , 2012; Schjenken & Robertson, 2014; Avila et al , 2015, see also Poiani, 2006), this is unlikely to be a general explanation for genetic variation in SFPs.…”
Section: Discussionmentioning
confidence: 53%
“…These studies have shown GEI on sperm characteristics such as sperm length (Morrow et al , 2008), sperm transfer rate (Engqvist, 2008), sperm velocity (Evans et al , 2015) and sperm mobility (Purchase et al , 2010), whereas others have focused on testis size as a predictor of sperm production (Nystrand et al , 2011; Marie-Orleach et al , 2017). To our knowledge, there is only one previous study that directly tested GEIs for seminal fluid transcript expression, our own previous investigation also in M. lignano (Patlar et al , 2019; but see also Mangels et al , 2015). Here, we therefore provide novel evidence of GEI for another major aspect of the male ejaculate of adaptive significance under sperm competition.…”
Section: Discussionmentioning
confidence: 99%
“…The HMWCs, namely SVS I–III, of mouse SVS form a major component in vaginal plug formation (Tseng et al, ). Recently, it has been reported that across a diversity of animals including rodents, male seminal fluid coagulates upon ejaculation to form the vaginal plug (Mangels et al, ). Although human ejaculates do not form as such vaginal plugs, they enter a phase of coagulation and liquefaction forming a semen coagulum that is analogous to the vaginal plug of mice (Aumuller & Riva, ; Peter, Lilja, Lundwall, Malm, & Semenogelin, ).…”
Section: Resultsmentioning
confidence: 99%
“…To expose the physiological significance of the copulatory plug, it is essential to understand its composition and formation mechanism. SVS forms the copulatory plug in most mammals (Chang et al, 2010;Dixson, 1998;Mangels et al, 2015;Ramm et al, 2008;Ramm, Parker, & Stockley, 2005). Evidence exists for the detection of SVS I-III in the copulatory plug of mice (Dean et al, 2009;Dean et al, 2011;Tseng et al, 2012).…”
mentioning
confidence: 99%